Overexpression of BIT33_RS14560 Enhances the Biofilm Formation and Virulence of Acinetobacter baumannii - Yang, Ruifu; Lai, Bipeng; Liao, Kang; Liu, Baomo; Huang, Lixia; Li, Shaoli; Gu, Jincui; Lin, Ziying; Chen, Yili; Wang, Shuaishuai; Qiu, Yanli; Deng, Jiating; et al. (Frontiers in Microbiology, 2022)
Acinetobacter baumannii, a strictly aerobic, non-lactose fermented Gram-negative bacteria, is one of the important pathogens of nosocomial infection. Major Facilitator Superfamily (MFS) transporter membrane proteins are a class of proteins that widely exists in microbial genomes and have been revealed to be related to biofilm formation in a variety of microorganisms. However, as one of the MFS transporter membrane proteins, little is known about the role of BIT33_RS14560 in A. baumannii. To explore the effects of BIT33_RS14560 on biofilm formation of A. baumannii, the biofilm formation abilities of 62 isolates were firstly investigated and compared with their transcript levels of BIT33_RS14560. Then, this specific gene was over-expressed in a standard A. baumannii strain (ATCC 19606) and two isolates of extensively drug-resistant A. baumannii (XDR-Ab). Bacterial virulence was observed using a Galleria mellonella infection model. High-throughput transcriptome sequencing (RNA seq) was performed on ATCC 19606 over-expressed strain and its corresponding empty plasmid control strain. Spearman’s correlation analysis indicated a significant negative correlation (R = -0.569, P = 0.000) between BIT33_RS14560 mRNA levels and biofilm grading of A. baumannii isolates. The amount of A. baumannii biofilm was relatively high within 12 to 48 hours. Regardless of standard or clinical strains, the biofilm biomass in the BIT33_RS14560 overexpression group was significantly higher than that in the control group (P＜0.0001). Kaplan-Meier survival curve analysis showed that the mortality of G. mellonella was significantly higher when infected with the BIT33_RS14560 overexpression strain (χ2 = 8.462, P = 0.004). RNA-seq showed that the mRNA expression levels of three genes including F3P16_RS12800, F3P16_RS04575 and F3P16_RS04585, which were related to bacterial adhesion, biofilm formation and virulence, were significantly up-regulated when BIT33_RS14560 was over-expressed. Our findings provided new insights in identifying potential drug targets for the inhibition of biofilm formation. We also developed a practical method to construct an over-expressed vector that can stably replicate in XDR-Ab isolates.